PENERAPAN MANAJEMEN PENDIDIKAN DALAM MEWUJUDKAN VISI SEKOLAH (STUDI DI SMP NEGERI 1 SALOMEKKO) - SARIL Saril (Adaara: Jurnal Manajemen Pendidikan Islam, 2018)
Abstract: Implementation of Education Management in Achieving Vision The school implements by conducting activities in each work unit so that it can be organized towards the same goal of allocating resources to develop and implement and sekolmpok people who are directed to work together for planning, organizing implementation and supervision. Facilitate the learning process, create program activities in schools, develop plans and quality improvement programs, evaluate the implementation, apply the system in accordance with the expectations of the school so that the regular learning process regularly with effective and efficient. The independence of professionalism to schools merupankan one factor to be able to encourage schools in menjujdukan vision and mission. Therefore, in applying a curriculum required by a strict, professional principal with strong management and leadership skills to be able to take decisions and initiatives to improve the quality of the school. Implementation of education management has been able to run well because seen from the vision and mission of the school is quite applicable by many teachers and students also can apply all that has terpapan in the future. Keywords: Management of Islamic Education and vision